2023
DOI: 10.1002/iid3.879
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TMUB1 blocks apoptosis and NF‐κB pathway‐mediated inflammation in recurrent spontaneous abortion

Abstract: Introduction Approximately 50% of cases with recurrent spontaneous abortion (RSA) have unexplained etiology. Aberrant expression of transmembrane and ubiquitin‐like domain containing 1 (TMUB1) is closely related to a series of diseases, including RSA. However, the function and underlying mechanism of TMUB1 in the occurrence of RSA has not been described. Methods TMUB1 expression was detected in the placental villous tissues of 30 women with normal miscarriages and 12 women with RSA. The pregnant mice were inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In recent years, research has highlighted the potential involvement of TMUB1 in several diseases, such as the inflammation-related recurrent spontaneous abortion [ 11 ]. Notably, studies have shown a connection between TMUB1 and colorectal cancer, which shows oncogenic potentials [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research has highlighted the potential involvement of TMUB1 in several diseases, such as the inflammation-related recurrent spontaneous abortion [ 11 ]. Notably, studies have shown a connection between TMUB1 and colorectal cancer, which shows oncogenic potentials [ 12 ].…”
Section: Introductionmentioning
confidence: 99%